Green Schools: The Impact of Sustainable Practices on Student Well-being - Ethan Blake; Jacob Alexander Scott (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Sustainable education environments, also known as "Green Schools," are designed to promote environmental awareness and improve student well-being. This paper investigates the effects of eco-friendly school infrastructures, green spaces, and sustainable curricula on students' mental health and academic performance. Findings indicate that green school initiatives enhance students’ cognitive functions, reduce stress, and promote pro-environmental behaviors.